2002
DOI: 10.1038/sj.onc.1205053
|View full text |Cite
|
Sign up to set email alerts
|

Anchorage-independent multi-cellular spheroids as an in vitro model of growth signaling in Ewing tumors

Abstract: Little is known about the growth-signaling pathways that govern the proliferation of Ewing tumor (ET) cells either in vitro or in vivo. We have studied signal transduction pathways in ET cell lines and compared kinase expression levels and proliferation rates with primary tumors. Cell lines were studied both as conventional adherent monolayers and as anchorage-independent multi-cellular spheroids. Importantly, we observed signi®cant di erences between these in vitro models and found that ET spheroids were more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 47 publications
5
66
1
Order By: Relevance
“…Phorbol 12-myristate 13-acetatestimulated HT29 cells, expressing high levels of COX-2, resulted to be able to degrade and migrate through ECM components of Matrigel-coated membranes, which indicates their malignant behaviour in vitro, associated with a well-described invasive and metastatic ability in vivo (Chen et al, 2001;Kakiuchi et al, 2002). Moreover, HT29 wild-type cells easily formed colonies in soft agar, which is an accepted criterion for transformation (Aaronson and Todaro, 1968) and an experimental condition that better represents tumour cells growth and invasiveness in vivo (Lawlor et al, 2002). The knockdown of COX-2 enzyme in HT29 cells abrogated their ability to invade Matrigel-coated membranes in a Boyden chamber assay, either in the absence or in the presence of PMA-stimulation, and strongly impaired their anchorageindependent growth in soft-agar basal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Phorbol 12-myristate 13-acetatestimulated HT29 cells, expressing high levels of COX-2, resulted to be able to degrade and migrate through ECM components of Matrigel-coated membranes, which indicates their malignant behaviour in vitro, associated with a well-described invasive and metastatic ability in vivo (Chen et al, 2001;Kakiuchi et al, 2002). Moreover, HT29 wild-type cells easily formed colonies in soft agar, which is an accepted criterion for transformation (Aaronson and Todaro, 1968) and an experimental condition that better represents tumour cells growth and invasiveness in vivo (Lawlor et al, 2002). The knockdown of COX-2 enzyme in HT29 cells abrogated their ability to invade Matrigel-coated membranes in a Boyden chamber assay, either in the absence or in the presence of PMA-stimulation, and strongly impaired their anchorageindependent growth in soft-agar basal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This antiangiogenic effect may in addition lead to enhanced sensitivity to chemotherapeutic agents such as taxol. Additionally, constitutive ERK activation has been shown not only in cells that overexpress Her2 but also in cells expressing EWS/FLI-1 chimeric proteins (35). Interfering with Her2-dependent signaling was shown to interfere with the constitutive activation of ERK-1/2 in EWS/FLI-1-expressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lawlor and colleagues demonstrated that EFT cell lines readily survive in anchorage-independent conditions, persisting as multicellular spheroid clusters [42]. These spheroids show considerable phenotypic differences from their monolayer counterparts, including dramatically reduced proliferation with associated suppression of cyclin D1 levels, greater dependence on serum stimulation, and hyperactivation of various oncogenic signaling pathways including the PI3K/Akt and Ras-ERK pathways.…”
Section: Anoikis Resistance In Eftsmentioning
confidence: 99%